O sentido da liberdade para adolescentes que cumprem medida de internação-sanção em decorrência de descumprimento da medida socioeducativa de semiliberdade - Silva, Márcia Rejane Oliveira de Mesquita (2011)
This is a study of adolescents who committed the infraction and received these institutions. Aims to understand the meaning of freedom for teens who violate free range measure and receive the detention-penalty. For this study took as a theoretical and methodological analysis of social theory and historical materialism expressed in Marx's work. However, due to the particular experiences of the adolescents in the socio-institutional, turned to Foucault, because he studied in depth the organization's disciplinary system. As the centrality of this study is the real subject, just to meet him, I used the interview as a resource. This method of research is part of my routine work on the condition of social justice. Three teenagers were interviewed - Gustavo, Aldo and Fabio - and their mothers. Fabio's mother agreed not recorded, but he accepted that I took note of his narrative. The recording of the interviews allowed the understanding of spontaneous speech and mode of expression of each interviewee. This thesis is organized into two parts. At first, I present the research universe and the theoretical and methodological. On Monday, the search result. The narratives of adolescents showed that the experience of deprivation of liberty (hospitalization-penalty) made the spontaneous expressions of everyday life had new dimension